2020
DOI: 10.1002/pc.25666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reinforcement architecture on the macroscopic mechanical properties of fiberous polymer composites: A review

Abstract: In order to curb the fuel consumption and corresponding CO2 emission, defence, automobile, and aerospace industries are leaning towards the use of light weight‐high stiffness engineered materials like fiber reinforced polymer composites (FRPCs). One of the major advantages of FRPCs is that various properties (stiffness, tensile strength, flexural strength, etc.) can be tailored according to requirements of the application. Architecture of the reinforcement used in FRPCs has been proved to affect these properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 98 publications
0
35
0
Order By: Relevance
“…[4,5] But polymer composites are accompanied by various drawbacks like complex fabrication, fiber delamination, low corrosion resistance, low thermal stability, low modulus, and strength, limiting its application to low load-bearing materials. [6][7][8] To relinquish the gap between the polymer composite services to the requirements of the application, utilization of nanoparticles for developing polymer nanocomposites is now being set forward. [9] Polymer nanocomposites are the composites produced by the combination of polymer matrix with the dispersion of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] But polymer composites are accompanied by various drawbacks like complex fabrication, fiber delamination, low corrosion resistance, low thermal stability, low modulus, and strength, limiting its application to low load-bearing materials. [6][7][8] To relinquish the gap between the polymer composite services to the requirements of the application, utilization of nanoparticles for developing polymer nanocomposites is now being set forward. [9] Polymer nanocomposites are the composites produced by the combination of polymer matrix with the dispersion of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In satin weave, the warp threads are raised above the weft threads, providing the fabric with a smooth surface and easy draping ability 0 [ 4 , 58 , 82 ]. Among the aforementioned types, twill exhibits higher flexural, tensile, and shear strengths [ 80 , 83 , 84 ]. Cavallaro showed that the use and proper arrangement of fabrics with different weaves (linen and twill as the outer layer and satin as the inner layer) can increase their resistance and energy absorption capacity compared to laminates containing fabrics of one type [ 85 ].…”
Section: Hybrid Compositesmentioning
confidence: 99%
“…Upon impact, they absorb and dissipate twice as much energy. Unlike 2D fabrics, the damage area is small and delamination is practically absent [ 3 , 83 , 86 , 87 ]. Among 3D fabrics, several types of structures are distinguished, of which orthogonal ones are the most popular and most commonly used as reinforcement in composites with increased mechanical strength.…”
Section: Hybrid Compositesmentioning
confidence: 99%
“…There are comprehensive and recent reviews about the fiber hybridization of polymer laminates in [7][8][9] where the mechanical and physical aspect of such laminates are discussed thoroughly. Therefore, herein, only some recent and most relevant efforts about fiber hybridization of CFRPs are reviewed briefly.…”
Section: Introductionmentioning
confidence: 99%